Resistant Staphylococcus aureus in intensive care unit (Research, Society and Development, 2023)
Objective: To evaluate the clinical and molecular profile of infections caused by resistant Staphylococcus aureus bacteria in intensive care units in Brazil. Methodology: The present study is an integrative literature review on the proposed theme, carried out in the PubMed\Medline, Scielo and Lilacs databases. Using the descriptors “staphylococcus aureus” AND “Resistant”. Research and reviews were included and letters to editors and reviews were excluded. Results: The increase in bacterial resistance to antimicrobials is a matter of increasing concern, especially in highly selective environments such as ICUs, due to the indiscriminate use of antibiotics and excessive procedures, which make health professionals carry microorganisms. Research shows that 70% of microorganisms are resistant to at least one antimicrobial. The group of these bacteria is named ESKAPES, among which is Staphylococcus aureus, object of this study. Colonizing the skin and nasopharyngeal fossa, gram-positive, it has a high prevalence in intensive care units and high virulence. In addition to easy dissemination, its adaptability has several foci, developing resistance to almost all classes of antibiotics, reaching the limit of treatment alternatives. Conclusion: Staphylococcus aureus is resistant to almost all available classes of antibiotics. Further studies on this pathogen and forms of dissemination are needed in order to avoid further damage, especially to ICU patients.